Cursing the Sacred: Debates on Islam and Blasphemy in Indonesia - Siddik, Syahril (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2021)
Islam and blasphemy have repeatedly emerged as the center of Indonesian public discourse and debate after the fall of Suharto. The debate becomes intense in a democratic society when people feel free to speak and deliver their opinions. When their speeches and opinions are regarded to have offences against a particular religion, the followers will protest against them. In Indonesia, these offences can be brought to court due to the presence of the blasphemy law in the Indonesian Criminal Code. Some scholars and religious leaders believe that the law have to be removed because it is not compatible with the principles of religious freedom and democracy. Others believe the law have to be defended because it is needed to regulate religious lives and maintain religious tolerance in the society. This article will investigate the diverse opinions among Muslim activists and leaders from various Muslim organizations including Nahdlatul Ulama, Muhammadiyah. This article attempts to answer two questions of what are the social and cultural backgrounds of the debates on blasphemy and how religious freedom is defined through these debates in contemporary Indonesia? The data are collected from the document and the recorded video of the judicial review of the blasphemy law in Indonesian constitutional court in 2010 and the interviews concerning the decision of the judicial review. This article suggests that religious freedom is limited by the majority of opinions in favor with the blasphemy law which discriminate free speech and religious minority groups